A Human Health Risk Assessment of Persistent Organic Pollutants in Wild Marine Mussels from the Western Cape Province of South Africa - Deborah Caitlin Firth; Philip E. Strydom; Lutz Auerswald; Louwrens Christiaan Hoffman (Foods)
Persistent Organic Pollutants (POPs) are contaminants that pose potential harm to environments and human consumers. Wild mussels (Mytilus galloprovincialis, Choromytilus meridionalis, and Perna perna) were collected from the coastline of the Western Cape Province of South Africa and analysed for polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs), and polyaromatic hydrocarbon (PAHs) via gas chromatography tandem mass spectrometry. The results showed eleven PAHs at concentrations ranging from NF to 50.3 ng g−1 d.w., five PCBs at concentrations between 4.1 and 18.6 ng g−1 d.w., and two OCPs, namely β-hexachlorocyclohexane (NF–7.9 ng g−1 d.w.) and chlordane (7.2–14.5 µg g−1 d.w.). A Human Health Risk Assessment (HHRA) determined PAH concentrations to pose little health risk to adults and children consuming < 1000 g and 500 g per month (g m−1) wild mussel meat, respectively. The HHRA of PCBs found adults and children would experience negative health effects at a consumption rate of 250 g m−1. HHRAs determined chlordane concentrations to pose unacceptable health risks for adults and children at all consumption rates (similar results for lindane). To avoid unnecessary POP-related health risks over a lifetime, it is recommended that adults consume < 250 g m−1 of wild mussels from the Western Cape Province, and children should avoid consuming mussels. This research demonstrates the legacy of POP contamination along the coastline of the Western Cape Province; more monitoring of these contaminants is imperative to protect marine ecosystems and food chains.